1981
DOI: 10.3177/jnsv.27.77
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of hemoglobin and work tolerance in iron-deficient subjects.

Abstract: SummarySelected parameters related to work tolerance were mea sured in 31 adult subjects with hemoglobin (Hb) concentration from 2.5 to 14.0g/100ml. Work tolerance was closely related to Hb concentration (r=0.74) regardless of the adequacy of storage iron level. One male and six females with a mean Hb of 3.5g/100ml (27-55 years old) were studied before and 24hr after transfusing 570ml of whole blood. The mean maximal work load tolerated increased 83% within 24hr after transfusion in these seven subjects. Post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 14 publications
1
33
1
Order By: Relevance
“…Physical work capacity in iron deficiency anemia might be elevated due to muscle training as well as skill in using the ergometer. The present results, which show no relationship between Hb concentrations and VO2 max, are inconsistent with previous observations by Edgerton et al (28) in which a close correlation was demonstrated. The Hb concentrations of their subjects were extremely low, between 2.5-8 g/100 ml, while they were 10-12g/100ml in the present experiment.…”
Section: Iron Deficiency Statuscontrasting
confidence: 57%
“…Physical work capacity in iron deficiency anemia might be elevated due to muscle training as well as skill in using the ergometer. The present results, which show no relationship between Hb concentrations and VO2 max, are inconsistent with previous observations by Edgerton et al (28) in which a close correlation was demonstrated. The Hb concentrations of their subjects were extremely low, between 2.5-8 g/100 ml, while they were 10-12g/100ml in the present experiment.…”
Section: Iron Deficiency Statuscontrasting
confidence: 57%
“…A linear relationship has been reported between iron deficiency and work capacity for agricultural workers in Colombia (39), Guatemala (40), Indonesia (41), Kenya (42,43), and Sri Lanka (44)(45)(46). Work capacity returned rapidly to normal with iron supplementation.…”
Section: Work Capacity and Productivitymentioning
confidence: 91%
“…Work capacity returned rapidly to normal with iron supplementation. Similarly, iron supplementation increased work output among road workers and rubber tappers in Indonesia (24); tea pickers in Indonesia (26,41) and Sri Lanka (44)(45)(46); agricultural workers in India (47), Guatemala (40), and Colombia (39); and industrial workers in Kenya (48), China (49), and other countries. Gains in productivity and take-home pay ranged from 10% to 30% of previous levels.…”
Section: Work Capacity and Productivitymentioning
confidence: 99%
“…The It has been shown that the greater the severity of anemia in humans and rats, the greater the decrement in work capacity (1)(2)(3)(4)(5)(6)(7)(8). Decreased O2 carrying capacity of blood (7) and decreased O2 utilizing capacity of tissues (1, 3, 9-11, 26, 27) decreased maximal capacity of O2 consumption (7).…”
Section: Discussionmentioning
confidence: 99%